Prevalence of visual impairment, blindness, and cataract surgery in the Hong Kong elderly. Issue 2 (1st February 2002) - Michon, John J; Lau, Joseph; Chan, Wing Shing; Ellwein, Leon B
Abstract : Background: The prevalence of vision impairment, unilateral/bilateral blindness, and cataract surgery were estimated in a population based survey among the elderly in a suburban area of Hong Kong. Methods: 15 public, private, and home ownership scheme housing estates in the Shatin area of Hong Kong were subjected to cluster sampling to randomly select a cross section of people 60 years of age or older. Visual acuity measurements and ocular examinations were conducted at a community site within each estate. The principal cause of reduced vision was identified for eyes with presenting visual acuity worse than 6/18. Results: A total of 3441 subjects from an enumerated population of 4487 (76.7%) completed an eye examination. The prevalence of presenting visual acuity less than 6/18 in at least one eye was 41.3%; and 73.1% in those 80 years of age or older. Unilateral blindness (acuity <6/60) was found in 7.9% of subjects and bilateral blindness in 1.8%. Refractive error and cataract were, respectively, the main causes of vision impairment and blindness. Visual impairment with either eye <6/18 increased with advancing age and was more prevalent in males, the less educated, and those living in public housing estates. The prevalence of cataract surgery was 9.1% and was associated with advancing age and less education. Conclusions: Blindness and visual disability were common in this socioeconomically advanced population, with most of it easily remedied. Because of a rapidly ageing population, healthcare planners in Hong Kong must prepare for an increasing burden of visual disability and blindness.